1981
DOI: 10.1007/bf00917800
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Problem Behavior in visually impaired children

Abstract: The Behavior Problem Checklist was completed by teachers of 104 students in a residential school for the visually impaired. Four separate factor analyses were performed. Additional analyses were conducted to determine the effect on the factor structure of sex, race, and age. Three factors that correspond to dimensions found in earlier research and previously labeled conduct disorder, personality problem, and inadequacy-immaturity were found. Overall, the visually impaired children tended to have problem behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…In contrast, Schnittjer and Hirshoren (1981) found that visually handicapped children had problem behavior patterns similar to nonhandicapped populations as judged by teachers' ratings. The discrepancy between their findings and our results may in part be attributable to the differences in age of the samples (children through adults in their sample) and the use of different measures (their use of the Behavior Problem Checklist).…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, Schnittjer and Hirshoren (1981) found that visually handicapped children had problem behavior patterns similar to nonhandicapped populations as judged by teachers' ratings. The discrepancy between their findings and our results may in part be attributable to the differences in age of the samples (children through adults in their sample) and the use of different measures (their use of the Behavior Problem Checklist).…”
Section: Discussionmentioning
confidence: 71%
“…Meighan, 1971 •ÏÏ¿ Î•È ÂÈ-̤ÚÔ˘˜ •˘ÙÔ•ÓÙÈÏ‹"ÂˆÓ Û ÙÔÌ›˜ fiˆ˜ Ô ÎÔÈ-ÓˆÓÈÎfi˜, Ô ÛˆÌ•ÙÈÎfi˜ Î•È Ô •Î•‰ËÌ•˚Îfi˜, ÛÂ Û ‡-ÁÎÚÈÛË Ì ÙÔ˘˜ ‚ϤÔÓÙ˜ ÂÊ‹‚Ô˘˜ (Lfipez-Justicia et al, 2001. Obiakor & Stile, 1990 (Wilhelm, 1989), ÙÔ Û˘ÓÔÏÈÎfi ‚•ıÌfi ÊÔ‚ÈÒÓ , Ù• ÌÔ-Ó٤ϕ ÚÔ‚ÏËÌ¿ÙˆÓ Û˘ÌÂÚÈÊÔÚ¿˜ (Schnittjer & Hirshoren, 1981. Teare, 1984, ÙË ‰ÂÍÈfiÙËÙ• ÂϤÁ¯Ô˘ Î•È ‰È¿ÊÔÚ˜ ÂÎÊ¿ÓÛÂȘ Û˘Ó•ÈÛıËÌ•ÙÈ-ÎÒÓ Î•È Û˘ÌÂÚÈÊÔÚÈÎÒÓ ‰˘ÛÎÔÏÈÒÓ (Kef, 2002.…”
mentioning
confidence: 99%
“…There are those who believe that blind children have no more psychological 'problems' than do the sighted (Schnittjer & Hirshoren 1981). Others concentrate on the vicissitudes of early development in otherwise normal blind infants -their sensitive periods, the organizing role of vision, and the perilous possibilities for arrested development without intervention (Burlingham 1972, Fraiberg 1977.…”
mentioning
confidence: 99%